Neurodevelopment at 1 year of age in infants with congenital heart disease - Dittrich, H (Copyright 2003 by Heart, 2003)
Objective: To assess psychomotor development and neurological sequelae in infants after surgery for congenital heart defects. Design and setting: Single institution prospective cohort study. Patients: 90 of 112 consecutive surviving infants of less than 1 year of age, without brain anomalies, conditions, or syndromes associated with delayed mental development, who underwent cardiac surgery during an 18 month period; 20 control infants with minor or no congenital heart defects. Main outcome measures: Griffiths developmental scales and standardised neurological examination at 1 year. Results: Mean (SD) developmental quotient (DQ) in index infants was 99 (10.6), compared with 106.7 (6.6) in controls (p < 0.001). DQ was lower in infants after palliative surgery (n = 16; 88 (12.2)) than after corrective surgery (n = 74; 101.4 (8.6)) (p < 0.001). Of the 90 index infants, 24 (27%) had a DQ below 93.5 (more than 2 SD below the mean of controls). Developmental delay (DQ < 93.5) was more common after palliative surgery (10/16, 63%) than after corrective surgery (14/74, 19%) (p < 0.001). Of the 90 index infants, 29 (32%) had neurological abnormalities, compared with only one of the 20 controls (5%) (p = 0.013). Neurological abnormalities were more frequent after palliative surgery (11/16, 69%) than after corrective surgery (18/74, 24%) (p < 0.001). Conclusions: There is a considerable rate of neurodevelopmental impairment at 1 year of age in infants after cardiac surgery. Psychomotor impairment and neurological sequelae are apparently more severe in infants in whom only palliative surgery is possible.